Numerical analysis of piled rafts with short bored piles - Oliveira,Eduardo Augusto dos Santos (2022)
Abstract Numerical analysis of the behavior of piled rafts seated on uniform soil with low bearing capacity has been important to support the project design. The calibration of the numerical model with instrumented load test allows usage of the results, in given conditions, in the foundation design of small and medium-sized buildings built on soils with the same mechanical properties analyzed in this paper. In this context, this paper evaluates numerical models, which allow to consider the influence of short bored piles connected to the raft. The models are also assessed using piled rafts concepts. From the results obtained, the load supported by the total shaft resistance is significant for the case of bored piles, and this load is from 14% to 30% higher in the case more flexible or thinner raft. Inserting piles in the rafts reduces settlement and increases overall stiffness. Such effects are amplified in piles with higher slenderness ratios (L/d).